THE IMPLEMENTATION OF DIGITAL STORYTELLING TO ENHANCE STUDENTS' SPEAKING ACHIEVEMENT AT JUNIOR HIGH SCHOOL - Azzahra, Melani Fathimah; Ifadah, Muhimatul; Budiastuti, Riana Eka (LEAD (Language, Education and Development), 2025)
This study aims to describe the implementation of digital storytelling to improve students' speaking achievement and to describe students' responses to the use of it. This study was conducted in the Classroom Action Research (CAR) design that occur in 2 cycles, involves students of ninth grade at SMP Muhammadiyah 3 Karangpandan as the research participant. The data were collected through observation, pre-tests, post-tests, and questionnaire. The results showed a significant increase in students' speaking achievement, represented by the score from pre-test to post-test in both cycles. In addition, students' responses collected through questionnaires revealed very positive perceptions: A high percentage of students agreed that digital storytelling makes them more confident when speaking (89.5% agree, 5.3% strongly agree and disagree, and 0% strongly disagree), helps them in improving their speaking (89.5% agree, 10.5% strongly agree, and 0% disagree and strongly disagree), helps them in conveying ideas (89. 5% agree, 5.3% strongly agree and disagree, 0% strongly disagree), affects their interest in learning speaking (89.5% agree, 5.3% strongly agree and disagree, 0% strongly disagree), will help to learn speaking (89.5% agree, 10.5% strongly agree, 0% disagree and strongly disagree). Students also found that digital storytelling has helpful in doing assignments and conveying ideas. Digital storytelling is proven to be effective in improving students' speaking achievement and fostered positive responses from students, triggering to be more active and confident when speaking English.